ROOT PERFORATIONS IN ENDODONTICALLY-TREATED POSTERIOR TEETH: A CONE-BEAM COMPUTED TOMOGRAPHY STUDY - Dana Bodnar; Anca Dragomirescu; Elena Zabrac; Cristina Coralia Nistor (Romanian Society of Oral Rehabilitation, 2024)
Root perforations represent artificial communication between the endodontic system and the periodontal space or the oral cavity. While it is true that they can reduce the success rates of endodontic treatment in the long term, nevertheless, with the new bioceramic materials, the evolution is promising. The aim of this retrospective study was to assess the prevalence of perforations in root canal-treated maxillary and mandibular posterior teeth based on findings from images taken using cone-beam computed tomography (CBCT) and to review the most predictable, appropriate non-surgical treatment procedures for the clinical management of these conditions, highlighting some relevant clinical cases of complex oral rehabilitation.